2023
DOI: 10.1007/s10802-023-01049-w
|View full text |Cite
|
Sign up to set email alerts
|

Processing Speed is Related to the General Psychopathology Factor in Youth

Abstract: The relationship between the p factor and cognition in youth has largely focused on general cognition (IQ) and executive functions (EF). Another cognitive construct, processing speed (PS), is dissociable from IQ and EF, but has received less research attention despite being related to many different mental health symptoms. The present sample included 795 youth, ages 11–16 from the Colorado Learning Disabilities Research Center (CLDRC) sample. Confirmatory factor analyses tested multiple p factor models, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 68 publications
2
5
0
Order By: Relevance
“…Our results are consistent with extensive literature demonstrating a relationship between general psychopathology ('p') and cognition (Bloemen et al, 2018;Brislin et al, 2022;Caspi et al, 2014;Castellanos-Ryan et al, 2016;Kramer et al, 2023;Martel et al, 2017;Romer & Pizzagalli, 2021). However, our analyses revealed that only the complex cognition domain was associated with general psychopathology.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results are consistent with extensive literature demonstrating a relationship between general psychopathology ('p') and cognition (Bloemen et al, 2018;Brislin et al, 2022;Caspi et al, 2014;Castellanos-Ryan et al, 2016;Kramer et al, 2023;Martel et al, 2017;Romer & Pizzagalli, 2021). However, our analyses revealed that only the complex cognition domain was associated with general psychopathology.…”
Section: Discussionsupporting
confidence: 92%
“…Difference in results may reflect different definitions of cognitive constructs. Kramer et al (2023) found that higher overall psychopathology was linked to poorer performance on processing speed tasks. However, certain tasks in their battery measure aspects of complex cognition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These could include basic cognitive processing speed. Research led by Lauren McGrath at the University of Denver published earlier this year found that slower processing speed was associated with general mental health symptoms in a group of nearly 800 young people with learning disabilities ( 3 ). Individuals with higher levels of p also tend to fare less well on tests requiring attention, concentration, and mental control, as well as visual-perceptual processing speed and visual-motor coordination, Caspi points out.…”
Section: Nature and Nurturementioning
confidence: 99%